2016
DOI: 10.1136/emermed-2015-204978
|View full text |Cite
|
Sign up to set email alerts
|

Time to presentation and 12-month health outcomes in patients presenting to the emergency department with symptoms of possible acute coronary syndrome

Abstract: Objective To define the association between time taken to present to the emergency department (ED) with symptoms of possible acute coronary syndrome (ACS) and 1-year outcomes. We also determined whether particular patient characteristics are associated with delays in seeking care after symptom onset. Methods We collected data, which included a customised case report form to record symptom onset, on adult patients presenting with suspected ACS to two EDs in Australia and New Zealand. Such patients were followed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 29 publications
1
7
1
Order By: Relevance
“…In another study, it has been shown that up to 33% of STEMI patients would wait > 12 h to seek medical care (20). Many other studies just simply reported the average time of delay (in minutes) (24)(25)(26). Compared to our data, we found that only 14% of ACS patients waited for > 12 h. It is worth noting that we did not stratify this group based on acute MI subtype due to sample size issues.…”
Section: Prevalence Of Delay In Seeking Carecontrasting
confidence: 83%
“…In another study, it has been shown that up to 33% of STEMI patients would wait > 12 h to seek medical care (20). Many other studies just simply reported the average time of delay (in minutes) (24)(25)(26). Compared to our data, we found that only 14% of ACS patients waited for > 12 h. It is worth noting that we did not stratify this group based on acute MI subtype due to sample size issues.…”
Section: Prevalence Of Delay In Seeking Carecontrasting
confidence: 83%
“…In Iceland, two to ten per cent of unexplained chest pain patients were diagnosed with CVD within 1 year . In a study of emergency department admissions of acute non‐coronary chest pain patients, five per cent of the patients developed an adverse CVD event over the first year . Among patients seen in rapid access chest pain clinics in England, 32% of CHD deaths (an average of 2.6 years from discharge) were to non‐cardiac chest pain patients .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the time it takes for the patient to realize the seriousness of the problem and seek medical attention – called pre‐hospital decision delay – can determine survival and subsequent recovery (Moser et al , ). Longer delays have been shown to predict worse patient outcomes one year after the cardiac event, including death or recurrent myocardial infarction (Cullen et al , ; De Luca, Suryapranata, Ottervanger, & Antman, ), and each half an hour of delay reduces patients’ life expectancy by about one year (Rawles, ).…”
Section: Introductionmentioning
confidence: 99%